Crystallization kinetics of an Au-based metallic glass upon ultrafast heating and cooling. (15th April 2017) - Bai, F.X.; Yao, J.H.; Wang, Y.X.; Pan, J.; Li, Y.
Abstract: The crystallization behavior of Au50 Cu25.5 Ag7.5 Si17 metallic glass during continuous heating/cooling and isothermal treatment is investigated by ultrafast calorimetry. The relationship between the transformation and the time/temperature scales of the alloy is established experimentally in a wide temperature range from glass transition temperature to the melting point. Temperature-dependent viscosity in the expanded supercooled liquid region is derived from the thermodynamic and kinetic analysis of the crystallization behavior of the metallic glass. The nucleation rate and growth velocity for crystallization of the supercooled liquid are analyzed by applying classical nucleation theory and diffusion-controlled growth theory. Graphical abstract: